Analyzing Medical Facilities in Primary Health Care Centers: Addressing the Gap in Access to Healthcare Services for Socio-economically Disadvantaged Populations (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In a resource-constrained society in developing countries like India, the value of health care infrastructure allocation is frequently undercut and disregarded. This research tries to assess the gap in accessing affordable health care services encountered by the socio-economically disadvantaged parts of society. This study argues that construction of additional facilities for responding to the rising demands of inhabitants in expanding cities is the need of the hour. We suggest a unique strategy for maximising the health care coverage of the peri-urban regions by building the smallest number of new public health care facilities. The southern perimeter, which was built in 1981 and has presently extended again in 2015, is totally bereft of public health care services. Based on our results we may assume that if the government increases the quality and availability of services at PHCs then it is more probable that individuals would pick PHCs for general healthcare-seeking. We feel that the results of the current research have substantial policy implications.